A study of the influence of brevetoxin exposure on trace element bioaccumulation in the blue mussel Mytilus edulis. (December 2018) - Pouil, Simon; Clausing, Rachel J.; Metian, Marc; Bustamante, Paco; Dechraoui-Bottein, Marie Yasmine
Abstract: Marine organisms are exposed to and affected by a multitude of chemicals present in seawater and can accumulate in their tissues a wide range of contaminants as well as natural biotoxins associated with harmful algal blooms (HABs). Trace elements and biotoxins may modify physiological functions in exposed organisms, and studies have been conducted to better understand their respective kinetics and effects in marine species. Despite the increasing concern of concurrent toxic HABs and pollution events due to anthropogenic pressures and global change, very little information is available on their combined effects. Chemical interactions between biotoxins and trace elements have been reported, and exposure to certain biotoxins is known to modify ion transport pathways, suggesting that biotoxins have the potential to alter trace element uptake. Using specific and sensitive radiotracer techniques (radioligand receptor binding assay and γ-spectrometry), this laboratory study examined the influence of pre-exposure to the brevetoxins (PbTxs)-producing microalgae Karenia brevis on the bioaccumulation of selected non-essential (Cd) and essential (Co, Mn and Zn) trace elements in the blue mussel Mytilus edulis . PbTxs are a group of neurotoxins known to accumulate in bivalves but also to have lethal effects on a number of marine organisms including fish and mammals. We found that, over 23 days exposure to the radiotracers, the bioaccumulation of the dissolved essential trace elements Co, Mn and Zn in M. edulis was not significantly affected by pre-exposure to toxic K. brevis . In contrast, the uptake rate constant ku of Cd was significantly higher in the pre-exposed group (p < 0.05), likely caused by a decrease in mussel clearance rates after K. brevis exposure. These results suggest that the effects of algal toxin exposure on bioaccumulation of trace elements in mussels may be trace element-dependent. Highlights: Brevetoxins (PbTx) can affected the bioaccumulation of non-essential metal in mussel. Uptake rate of Cd in mussel is significantly higher after PbTx exposure. Body distribution of metals is not affected by the brevetoxins.